Dexmedetomidine use in patients undergoing electrophysiological study for supraventricular tachyarrhythmias. Issue 1 (25th October 2016) - Tirotta, Christopher F.; Nguyen, Tuan; Fishberger, Steven; Velis, Evelio; Olen, Melissa; Lam, Lourdes; Madril, Danielle R.; Hughes, Jessica; Lagueruela, Richard G.
Summary: Background: Dexmedetomidine is a selective alpha‐2 adrenergic agonist with sedative, analgesic, and anxiolytic properties. Dexmedetomidine has not been approved for use in pediatrics. Dexmedetomidine has been reported to depress sinus node and atrioventricular nodal function in pediatric patients; it has been suggested that the use of dexmedetomidine may not be desirable during electrophysiological studies. Aim: We hypothesize that the use of dexmedetomidine does not inhibit the induction of supraventricular tachyarrhythmias (SVT) during electrophysiological studies and does not inhibit the ablation of such arrhythmias. Methods: In this retrospective, observational cohort study, we reviewed all cases presenting to the cardiac catheterization laboratory for diagnosis or treatment of SVT since 2007. All cases were performed by the same electrophysiologist. The anesthesia was provided by one of the three cardiac anesthesiologists. One cardiac anesthesiologist did not use dexmedetomidine during electrophysiological studies. A second used dexmedetomidine, but only with an infusion. The third used dexmedetomidine with a primary bolus and an infusion. Thus, the patients were stratified into three different groups: Group 1 patients did not receive any dexmedetomidine. Group 2 patients received a dexmedetomidine infusion of 0.5–1 μg·kg −1 ·h −1 . Group 3 patients received a dexmedetomidine infusion of 0.5–1 μg·kg −1 ·h −1 and a dexmedetomidine bolus prior to the infusion of 0.5–1 μg·kg −1 . We then compared those patients for the following variables: demographic data including age, sex, height, weight; anesthetic data such as, mask vs intravenous induction, identity of induction agent, amount of sevoflurane and propofol used; amount of dexmedetomidine used; presence of congenital heart disease and other comorbidities; the need for isoproterenol and dose, the need for adenosine and dose, and the need for any other medications to affect rhythm both before and after radiofrequency ablation; the ability to induce the arrhythmia, the type of arrhythmia, the presence of Wolff–Parkinson–White syndrome, the presence of an accessory pathway, the ablation rate, and the recurrence rate. Results: There was no difference in the anesthetic agents, except there was a lesser amount of propofol used in the dexmedetomidine groups ( χ 2 (2) = 48.2, P < 0.001). There was no difference in the electrophysiological parameters among groups, except the Group 1 patients did require the use of isoproterenol in the preablation period less often compared to the dexmedetomidine groups ( χ 2 (2) = 15.2, P < 0.01). However, with the greater use of isoproterenol, there was no difference in the ability to induce the arrhythmia. Moreover, the percentage of patients ablated, and the recurrence rate among groups was the same. Conclusions: We conclude that dexmedetomidine does not interfere with the conduct of electrophysiological studies for SVT and the successful ablation of such arrhythmias. However, dexmedetomidine use did result in a greater need for isoproterenol. Abstract :